Organización contable en la Empresa Comercial “San Antonio” de la ciudad de Zamora, periodo de octubre a diciembre de 2022. - Reyes Villavicencio, Josefa Gicella (2023)
The Curricular Integration Work entitled ACCOUNTING ORGANIZATION IN THE COMMERCIAL COMPANY "SAN ANTONIO" OF THE CITY OF ZAMORA, PERIOD FROM OCTOBER TO DECEMBER 2022, was developed in order to collect, organize and record all the information of its economic movements. This work was carried out in compliance with the specific objectives, designing a plan and manual of accounts according to the needs and activities of the company. The accounting process was developed with the compilation of the source documentation, the initial inventory was made where the merchandise, rights and obligations are verified, to elaborate the Initial Situation Statement and continue with the registration in the daily book with its respective majorization, verification balance, work sheet and financial statements with its corresponding explanatory notes. And finally, with the information obtained in the financial statements, the basic financial indicators of liquidity, activity, leverage and profitability were applied, analyzing the economic and financial performance of the company. The methodology used had a mixed orientation, being of an exploratory and descriptive level since it helps to know the conditions of the company, its design is non-experimental in which the inductive, deductive, analytical, synthetic, descriptive, mathematical method was used, and techniques such as observation, interview and information gathering. The results obtained from the application of the accounting process showed a value in assets of $264.863,24, liabilities of $72.459,82, equity of $192.403,42, income of $42.148,46 and expenses of $37.057,87, obtaining a net profit for the year of $4.327,00, results that allowed the application of financial indicators in order to know its economic and financial situation. Finally, the conclusions and recommendations of the results obtained are presented, in order to help the owner to make the right decisions to strengthen her business.